Abnormal transport properties of Bi-III superconducting phase in pressurized bismuth single crystal. (31st May 2021) - Zhang, Yufeng; Gouchi, Jun; Ishigaki, Kento; Nagasaki, Shoko; Shi, Zhixiang; Uwatoko, Yoshiya
Abstract: Resistivity, magnetoresistance, and upper critical field, have been comprehensively studied for the bismuth (Bi)-III superconducting phase in the pressure range of 2.9 GPa ⩽ P ⩽ 6.2 GPa. It is discovered that the transition temperature T c of the Bi-III phase is gradually suppressed with increasing pressure. Strikingly, the temperature-dependent resistivity above T c in the Bi-III region reveals notable non-Fermi-liquid behaviors, resembling many unconventional superconducting systems. As the pressure increases, the magnetoresistance effect progressively grows and reaches a maximum value of 212% at pressure ∼6.2 GPa and field of 5 T, indicating a possible contribution to the charge conduction by Dirac electrons. Moreover, the zero-temperature upper critical field for the Bi-III phase displays relatively low values concerning the moderate T c values, and the reduced upper critical field for different pressures deviates from the single-band Werthamer–Helfand–Hohenberg model. These unusual normal state transport properties and unique behavior of the upper critical field point to possible unconventional superconductivity for the Bi-III superconducting phase.